Trade Opportunity of Potential Agricultural Commodities between Turkey and Indonesia (Case Study Palm Oil) - Haryadi, Hari; OGUZ, Cennet (Indonesian Journal of Agricultural Research, 2019)
This research was conducted in Indonesia and Turkey. The aims of this study is to analyse the Strengths, Weaknesses, Opportunities, and Threats (SWOT) of trade relations in, the industry attractiveness, trade potential, strategic orientation of the palm oil commodities traded between Turkey and Indonesia, and to analyse the industry competitive forces. This research use primary and secondary data, both of quantitative and qualitative ones. The primary data obtained from deep interview by purposive sampling, Focus Group Discussion (FGD) method by online and offline communication, and from experts acquisition. The secondary data obtained from UN Comrade, FAOSTAT, IMF, World Bank, Ministry of Commerce, Ministry of Agriculture and other relevant agencies. Descriptive data were analysed using the SWOT Matrix method, the SOR (Strategic Orientation) Matrix method, Strategic Position and Action Evaluation (SPACE), and the Porter’s Five Competitive Forces Matrix. Based on the diagram by the internal-external factor matrix, it is known that the condition of between Turkey and Indonesia were same condition on the Divest.